2021
DOI: 10.1002/pc.25984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanate on the bonding properties of silicone rubber and polyester fabric

Abstract: The effects of titanate on the mechanical properties of silicone rubber and peel strength of polyester fabric with silicone rubber are studied. The tests show that the hardness and mechanical properties of silicone rubber containing 0.2 phr titanate are similar to those of pure silicone rubber, and the peel strength (1.11 N/mm) between fabric and rubber matrix without inner fabric is the highest in the test groups. Fourier transform infrared spectra (FT-IR) and contact angle test indicate that the surface wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the WCA test under an air environment, the sealing gas in the valley was considered not to be wetted by water, that is, the air-WCA was considered to be 180 . Therefore, Equation ( 1) could be written as Equation (2).…”
Section: Robustness Of Modified Silicone Rubber Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the WCA test under an air environment, the sealing gas in the valley was considered not to be wetted by water, that is, the air-WCA was considered to be 180 . Therefore, Equation ( 1) could be written as Equation (2).…”
Section: Robustness Of Modified Silicone Rubber Surfacesmentioning
confidence: 99%
“…The hydrophobicity of the material surface is an old and young topic and has an important impact on the application of materials in a natural environment 1,2 . Water erosion has a significant impact on the service life of water absorbent and hygroscopic materials (including wood, fiber composites, and metal materials) 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Interface bonding involves sticking two different materials to each other with the help of adhesives or interaction. Generally, the bonding properties of composites depend upon surface wettability and compatibility of the two different materials . However, few studies have focused on interface bonding between PDMS and other materials. , As a result of low surface energy, the PDMS surface is hard to wet and bond by conventional primers [such as PU, polyethylenimine, poly­(vinyl alcohol), polyacrylate, and epoxy resins] during real-life applications.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the bonding properties of composites depend upon surface wettability and compatibility of the two different materials . However, few studies have focused on interface bonding between PDMS and other materials. , As a result of low surface energy, the PDMS surface is hard to wet and bond by conventional primers [such as PU, polyethylenimine, poly­(vinyl alcohol), polyacrylate, and epoxy resins] during real-life applications. The undercoating treatment may be a simple way to bond the polypropylene surface, which could be a cost-efficient method to improve adhesion between the silicone leather and PDMS surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the improvement in bonding between NBR and PET is due to the formation of covalent bonds at the rubber/ fabric interface. Han et al [12] used titanate to improve the adhesion properties between silicone rubber and polyester fabric. The hardness and tensile strength of the silicone rubber composite decreased gradually as the titanate content increased, whereas the peel force increased up to a titanate concentration of 0.2%.…”
Section: Introductionmentioning
confidence: 99%